2019
DOI: 10.1007/s11011-018-0363-7
|View full text |Cite
|
Sign up to set email alerts
|

Vernonia Amygdalina Del. stimulated glucose uptake in brain tissues enhances antioxidative activities; and modulates functional chemistry and dysregulated metabolic pathways

Abstract: Brain glucose uptake is usually reduced in type 2 diabetes owing to downregulation of brain glucose transporters. The ability of Vernonia amygdalina to stimulate glucose uptake as well as ameliorate glucose-induced oxidative stress and proinflammation were investigated in rat brain. Hot infusion of V. amygdalina leaves was incubated with rat brain tissues for 2 h in the presence of glucose. Another incubation with glucose only, served as negative control while metformin served as positive control. Incubation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 64 publications
4
23
0
Order By: Relevance
“…With the effect of Vernonia amygdalina that contains the structure of terpenoids on the cells of the rat brain tissue, it has been shown that in conditions of HG uptake in these cells, the amount of ROS increased, the amount of glutathione decreased, and thus the amount of NO also changed 83. Therefore, increased antioxidant availability may be helpful in preventing or slowing the progress of various oxidative stress-related diseases 84…”
Section: Discussionmentioning
confidence: 99%
“…With the effect of Vernonia amygdalina that contains the structure of terpenoids on the cells of the rat brain tissue, it has been shown that in conditions of HG uptake in these cells, the amount of ROS increased, the amount of glutathione decreased, and thus the amount of NO also changed 83. Therefore, increased antioxidant availability may be helpful in preventing or slowing the progress of various oxidative stress-related diseases 84…”
Section: Discussionmentioning
confidence: 99%
“…72 Also, it was capable of stimulating glucose uptake in rat brain as well as showing neuroprotective effects. 73…”
Section: Discussionmentioning
confidence: 99%
“…The nitric oxide (NO) level of the experimental tissue samples was determined using the Griess method as previously described. [1,28] Briefly, 100 μl of brain supernatant or distilled water (serving as the blank) was added to equal volume of Griess reagent and incubated for 30 min at 25°C in the dark. Absorbance was then read at 548 nm.…”
Section: Determination Of Nitric Oxide Levelmentioning
confidence: 99%
“…Oxidative stress is amongst the major drivers of complications associated with the pathogenesis of neurodegenerative diseases such as Alzheimer's and Parkinson's diseases. [1,2] This has been attributed to the dependency of the brain on glucose and oxygen (O 2 ), coupled with its high polyunsaturated fatty acids, low endogenous antioxidant system and redox-active metal load. [3,4] Of these redox-active metals, iron has been reported to be one of the most potent prooxidants.…”
Section: Introductionmentioning
confidence: 99%